UPPER CRETACEOUS DEPOSITS IN EASTERN PIEDMONTS OF THE LESSER CAUCASUS - Gasanov T.Ab.; Melikov O.G.; Babaev Sh.A.; Aliev G.A. (My University, 2002)
The Upper Cretaceous sequence in the east of the Lesser Caucasus, within the Azerbaijan territory, begins with the Cenomanian terrigenous sediments that are overlain with a hiatus by thick volcanogenic-terrigenous deposits of the Coniacian and Santonian stages. The Campanian-Maastrichtian interval and lower Paleocene are composed mainly of limestones bearing echinoids, inocerams, and planktonic foraminifers, which are used to distinguish the substages. Boreholes between the Agdam and Fizuli cities and near the town of Terter recovered the Maastrichtian and lower Paleocene limestones below the Akchagylian cover.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая